DNMBP-AS1/hsa-miR-30a-5p/PGC1α axis suppresses tumor progression of colorectal cancer by inhibiting PKM2-mediated Warburg effect and enhance anti-PD-1 therapy efficacy - Tianxiao Wang; Wenxin Zhang; Jiafeng Liu; Xiang Mao; Xinhai Wang; Jiyifan Li; Yuxin Huang; Zimei Wu; Haifei Chen; Huanying Shi; Huijie Qi; Lu Chen; et al. (Cell Death Discovery)
Abstract The Warburg effect, which is aerobic glycolysis, constitutes a major driver of various cancer progression. Therefore, we aimed to examine the role of peroxisome proliferator-activated receptor-gamma coactivator-1α (PGC1α) and its competing endogenous RNA (ceRNA) network in colorectal cancer (CRC) metabolic reprogramming. We used bioinformatics analysis and dual-luciferase reporter gene experiments and identified the DNMBP-AS1/hsa-miR-30a-5p/PGC1α ceRNA network. Additionally, we investigate the impact of PGC1α expression alterations on CRC proliferation and metabolic reprogramming. Moreover, we studied the influence of PGC1α on pyruvate kinase M2 (PKM2), and CRC malignant behavior manifestation. Our study has uncovered a significant association between the DNMBP-AS1/hsa-miR-30a-5p/PGC1α ceRNA network and CRC patient prognosis. Additionally, PGC1α overexpression impeded CRC growth, reduced glycolytic capacity, and enhanced anti-PD-1 therapy efficacy. PGC1α inhibited tumor cell glycolysis by downregulating the WNT/β-catenin pathway depending on peroxisome proliferator-activated receptor gamma (PPARγ), thereby suppressing PKM2. The PPARγ agonist rosiglitazone could hinder CRC proliferation and glycolytic activity. Combined with the PGC1α agonist ZLN005, it exhibits synergistic effects for treating CRC. Moreover, we verified that ZLN005 significantly potentiated PD-1 induced tumor suppression in xenograft mice. Finally, we demonstrated that PGC1α and PKM2 expression patterns in tumor tissues were closely related to patient prognosis. Moreover, we constructed a predictive model to predict the 5-year survival events in CRC patients using random forest model. Our results offer novel perspectives on the role of DNMBP-AS1/hsa-miR-30a-5p/PGC1α network in controlling CRC proliferation, metabolism and immune responses. Furthermore, our investigation reveals that using rosiglitazone combined with PGC1α agonist presents a promising therapeutic approach for managing CRC.